2018
DOI: 10.1080/03009734.2018.1539054
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic epidural anaesthesia reduces insulin resistance and inflammatory response in experimental acute pancreatitis

Abstract: Aims: The activity of the sympathetic nervous system (SNS) is crucial at an early stage in the development of an inflammatory reaction. A study of metabolic events globally and locally in the early phase of acute pancreatitis (AP), implying hampered SNS activity, is lacking.We hypothesized that thoracic epidural anaesthesia (TEA) modulates the inflammatory response and alleviates the severity of AP in pigs.Material and methods: The taurocholate (TC) group (n = 8) had only TC AP. The TC + TEA group (n = 8) had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…On analysis, they concluded that TEA led to improved survival, enhanced microcirculatory perfusion, and improved tissue oxygenation with less histopathologic tissue damage in the TEA group. Winsö et al randomized 16 pigs with induced acute pancreatitis into two groups: group 1- no intervention, group 2- TEA to investigate the efficacy of TEA to reduce insulin resistance and inflammatory response in presence of acute pancreatitis [ 35 ]. Blood sugar levels, serum insulin concentration, serum lipase, and relative tissue oxygen tension (PtiO2) levels were compared in both groups.…”
Section: Reviewmentioning
confidence: 99%
“…On analysis, they concluded that TEA led to improved survival, enhanced microcirculatory perfusion, and improved tissue oxygenation with less histopathologic tissue damage in the TEA group. Winsö et al randomized 16 pigs with induced acute pancreatitis into two groups: group 1- no intervention, group 2- TEA to investigate the efficacy of TEA to reduce insulin resistance and inflammatory response in presence of acute pancreatitis [ 35 ]. Blood sugar levels, serum insulin concentration, serum lipase, and relative tissue oxygen tension (PtiO2) levels were compared in both groups.…”
Section: Reviewmentioning
confidence: 99%
“…[5][6][7] However, knowledge is lacking for some commonly used anaesthetic protocols in pigs and glucose-stimulated conditions have only been studied to a very limited extent in pigs. 8,9 Some anaesthetic drugs used in pre-clinical animal models are known to affect glucose metabolism by inhibition of insulin release and/or induction of insulin resistance, [10][11][12][13][14] making general anaesthesia a potential confounding factor in glucose metabolism studies.…”
Section: Introductionmentioning
confidence: 99%
“…3 Previous studies have demonstrated that thoracic epidural analgesia (TEA) could improve pancreatic and splanchnic perfusion. [4][5][6] A recent multicentre study showed that TEA reduced the mortality of patients with AP. 7 However, only 46 patients who received TEA were included in this study.…”
Section: Introductionmentioning
confidence: 99%